2018
DOI: 10.1371/journal.pone.0190388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mode of delivery on pregnancy outcomes in women with premature rupture of membranes after 28 weeks of gestation in a low-resource setting: A prospective cohort study

Abstract: BackgroundDespite the high prevalence of premature rupture of membranes (PROM) in low-resource settings, the preferred mode of delivery remains unclear. We compared the perinatal mortality in a prospective cohort of women with PROM after 28 weeks following vaginal or caesarean delivery at Mulago Hospital with the aim of adopting evidence based practice and improving patient care.MethodsBetween November 2015 and May 2016, 1455 women with PROM after 28 weeks of gestation and their newborns were prospectively fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
4
15
3
Order By: Relevance
“…The prevalence of PROM among women above 28 weeks of gestation admitted at KIU-TH was 13.8%. This prevalence of PROM lies within the worldwide range of 5 to 15% as reported by Huang et al [3] and Shadma and Aymen [4] although it is higher than that reported by Maryuni [14] in Indonesia (10%), Abouseif et al [19] in Egypt (4.7%), and Kayiga et al [10] in Mulago Hospital in central Uganda (12.1%). This discrepancy was attributed to the contextual differences in the study setting.…”
Section: Discussion Of the Findingssupporting
confidence: 50%
See 2 more Smart Citations
“…The prevalence of PROM among women above 28 weeks of gestation admitted at KIU-TH was 13.8%. This prevalence of PROM lies within the worldwide range of 5 to 15% as reported by Huang et al [3] and Shadma and Aymen [4] although it is higher than that reported by Maryuni [14] in Indonesia (10%), Abouseif et al [19] in Egypt (4.7%), and Kayiga et al [10] in Mulago Hospital in central Uganda (12.1%). This discrepancy was attributed to the contextual differences in the study setting.…”
Section: Discussion Of the Findingssupporting
confidence: 50%
“…where n is the desired sample size, z α is the z-statistic at α = 1:96 (95% level of confidence), z β is the z-statistic at β = 0:84, p is the prevalence of PROM in Uganda (12.1%) [10], and d is the level of precision (0.05). Therefore, n = ðð1:96 + 0:84Þ 2 × 0:121 ð1 − 0:121ÞÞ/ ð0:05Þ 2 = 334.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This genetic link may explain the occurrence of repeated events of rupture of membranes in a woman. Our study found that there was no difference in the mode of delivery in the study and the control group, like Sharma and Mehta [3] did, while other studies [22,23] reported higher rate of caesarean deliveries among women with PPROM. Poor perinatal outcomes were observed in our study group, consistent with results of another study [24].…”
Section: Discussioncontrasting
confidence: 48%
“…The protective effect of PROM could reflect timely management of such pregnancies considering that these deliveries were attended at a tertiary care facility where comprehensive emergency obstetric and newborn care (CEmONC) services are available. Despite that, a study in Uganda has shown that CS delivery, particularly among women with PROM, increases the risk of perinatal mortality among other adverse pregnancy outcomes [52].…”
Section: Plos Onementioning
confidence: 98%